The Influence of Information and Communication Technology (ICT) Media on the Economics Learning Outcomes of Grade XI Students at SMA Negeri Ploso - Fika Lutfiana; Siti Munawaroh (Darul Yasin Al Sys, 2026)
Although Information and Communication Technology (ICT) has become increasingly important for improving instructional quality and students’ academic achievement, empirical evidence regarding its effectiveness remains necessary across diverse educational contexts. This study aims to examine the effect of ICT utilization on the learning outcomes of Grade XI students at SMA Negeri Ploso. A quantitative explanatory approach was employed, involving 101 students selected through total sampling. Data were collected through questionnaires, observations, interviews, and documentation and analyzed using simple linear regression with IBM SPSS Statistics 27. The findings demonstrate that ICT utilization has a positive and statistically significant effect on students’ learning outcomes (p < .001), with a coefficient of determination (R²) of .715, indicating that ICT accounts for 71.5% of the variance in learning outcomes. These results confirm that effective ICT utilization contributes substantially to improving students’ academic performance. The study concludes that the sustained integration of ICT into instructional practices is essential for promoting more effective, interactive, and student-centered learning. These findings provide empirical support for schools and educators to strengthen ICT-based instructional strategies and optimize digital learning environments at the senior high school level.